History, politics and vulnerability: explaining excess mortality in Scotland and Glasgow. (October 2017) - Walsh, D.; McCartney, G.; Collins, C.; Taulbut, M.; Batty, G.D.
Abstract: Objectives: High levels of excess mortality (i.e. that not explained by deprivation) have been observed for Scotland compared with England & Wales, and especially for Glasgow in comparison with similar post-industrial cities such as Liverpool and Manchester. Many potential explanations have been suggested. Based on an assessment of these, the aim was to develop an understanding of the most likely underlying causes. Note that this paper distils a larger research report, with the aim of reaching wider audiences beyond Scotland, as the important lessons learnt are relevant to other populations. Study design: Review and dialectical synthesis of evidence. Methods: Forty hypotheses were examined, including those identified from a systematic review. The relevance of each was assessed by means of Bradford Hill's criteria for causality alongside—for hypotheses deemed causally linked to mortality—comparisons of exposures between Glasgow and Liverpool/Manchester, and between Scotland and the rest of Great Britain. Where gaps in the evidence base were identified, new research was undertaken. Causal chains of relevant hypotheses were created, each tested in terms of its ability to explain the many different aspects of excess mortality. The models were further tested with key informants from public health and other disciplines. Results: In Glasgow's case, the city was made more vulnerable to important socioeconomic (deprivation, deindustrialisation) and political (detrimental economic and social policies) exposures, resulting in worse outcomes. This vulnerability was generated by a series of historical factors, processes and decisions: the lagged effects of historical overcrowding; post-war regional policy including the socially selective relocation of population to outside the city; more detrimental processes of urban change which impacted on living conditions; and differences in local government responses to UK government policy in the 1980s which both impacted in negative terms in Glasgow and also conferred protective effects on comparator cities. Further resulting protective factors were identified (e.g. greater 'social capital' in Liverpool) which placed Glasgow at a further relative disadvantage. Other contributory factors were highlighted, including the inadequate measurement of deprivation. A similar 'explanatory model' resulted for Scotland as a whole. This included: the components of the Glasgow model, given their impact on nationally measured outcomes; inadequate measurement of deprivation; the lagged effects of deprivation (in particular higher levels of overcrowding historically); and additional key vulnerabilities. Conclusions: The work has helped to further understanding of the underlying causes of Glasgow's and Scotland's high levels of excess mortality. The implications for policy include the need to address three issues simultaneously: to protect against key exposures (e.g. poverty) which impact detrimentally across all parts of the UK; to address the existing consequences of Glasgow's and Scotland's vulnerability; and to mitigate against the effects of future vulnerabilities which are likely to emerge from policy responses to contemporary problems which fail sufficiently to consider and to prevent long-term, unintended social consequences. Highlights: High levels of excess mortality in Scotland & Glasgow compared with elsewhere in UK. We investigate 40 previously proposed hypotheses to identify the underlying causes. Glasgow made more vulnerable to key socio-economic and political exposures. Vulnerability caused by a series of adverse historical factors and decisions. Findings re-emphasise the importance of political economy for population health.